ChemInform Abstract: Ligand‐Promoted C(sp3)—H Olefination en Route to Multi‐Functionalized Pyrazoles. Issue 40 (September 2016) - Yang, Weibo; Ye, Shengqing; Schmidt, Yvonne; Stamos, Dean; Yu, Jin‐Quan
Abstract: A broad spectrum of pyrazole substrates bearing a quaternary carbon center at position 3 and analogue (VIa) are successfully olefinated in the presence of the amino acid ligand AIL with Cu(O‐Ac)2 as the terminal oxidant.